Preparation and Evaluation of Antioxidant Properties of Schiff Base With Co(II) and Pd(II) Metal Complexes - Colak, Naki; Savci, Ahmet; Buldurun, Kenan; Turan, Nevin (Wiley-V C H Verlag Gmbh, 2026)
In this study, a Schiff base ligand was synthesized from methyl-2-amino-4-ethyl-5-methylthiophene-3-carboxylate and 5-chloro-2-hydroxybenzaldehyde, and its Co(II) and Pd(II) complexes were prepared. The structures of the ligand and complexes were characterized using FT-IR, 1H/13C-NMR, UV-vis, ESI-MS, TGA, powder XRD, elemental analysis, magnetic susceptibility, and molar conductivity. By mixing the ligand with CoCl2 & centerdot;6H2O and PdCl2(CH3CN)2 in a 1:1 molar ratio, the corresponding complexes were formed. Spectroscopic data showed the Co(II) complex is distorted tetrahedral and the Pd(II) complex is square-planar, each with one coordinated water. Molar conductance confirmed that both complexes are non-electrolytes. The in vitro antioxidant activities of the ligand and its metal complexes were studied at 25, 50, and 100 & micro;g/mL, using CUPRAC, ABTS, FRAP, and DPPH assays, compared with standard antioxidants. Activity indices allowed direct comparison with standards. CUPRAC and ABTS showed similar trends, while FRAP and DPPH indicated higher activity for standard antioxidants. In the FRAP, L (0.76 & micro;g TE/mL), Co(II) (0.44 & micro;g TE/mL), and Pd(II) (0.74 & micro;g TE/mL) were lower than BHA (5.46 & micro;g TE/mL) and AA (4.70 & micro;g TE/mL). In DPPH, Pd(II) showed the lowest radical scavenging activity (IC50: 54.40 & micro;g/mL), while AA had the highest (IC50: 1.30 & micro;g/mL).
Keywords: Antioxidant Activities; Co(Ii) And Pd(Ii) Complexes; Frap; Non-Electrolyte; Schiff Base